The Relationship between Energy Drink Consumption Dependence, Alcohol Consumption Level, and Obesity on the Incidence of Hypertension - Arduta, Firmandito Satya; Utama, Lalu Buly Fatrahady; Wiatma, Deny Sutrisna; Suanjaya, Made Agus (CV. Global Health Science Group, 2024)
Hypertension is non-communicable disease with high and increasing incidence. Based on the Profile Book of Asy-Syifa' West Sumbawa Hospital 2022, there were 2686 cases of hypertension. Dependence on energy drink consumption, alcohol consumption level, and obesity play a role in causing hypertension through their effects on impaired cardiac output and vascular resistance. This research aimed to analyse the relation between dependence energy drink consumption, alcohol consumption level, and obesity to the incidence of hypertension at Asy-Syifa' Hospital, West Sumbawa. The research utilized an observational analytical approach utilizing a cross-sectional study design. A total of 75 samples were chosen through a purposive sampling method, adhering to the inclusion and exclusion criteria. Data was gathered using questionnaires, BMI results, and patient blood pressure examination results. The data was analyzed using the Chi-Square correlation test. The analysis results indicated a correlation between dependence on energy drink consumption and its association with the incidence of hypertension in Asy-Syifa' West Sumbawa Hospital (p = 0.026). There is an association between alcohol consumption levels and the incidence of hypertension in Asy-Syifa' Hospital West Sumbawa (p = 0.002). There is an association between obesity and the incidence of hypertension in Asy-Syifa' Hospital West Sumbawa (p = <0.001).